Visual Semiotics and Learner Engagement in Technology Mediated Language Education - Zaqhid, Ahmad Aqsal (Pemuda Peduli Publikasi Insan Ilmiah, 2025)
Purpose: This study aimed to investigate the role of visual semiotics in shaping learner engagement within technology-mediated language education. It sought to explore how visual elements such as images, icons, animations, and color-coded cues influence cognitive, emotional, and behavioral engagement, as well as how learners interpret and make meaning from these semiotic resources. Subjects and Methods: The study employed a qualitative case study design involving 10–15 language learners participating in digital language learning activities. Data were collected through observations, semi-structured interviews, and analysis of digital learning materials. Observations focused on learners’ interactions with visual semiotic elements, interviews captured learners’ subjective experiences and interpretations, and material analysis identified semiotic features embedded in the digital platform. Data were analyzed using thematic coding and semiotic analysis to identify patterns in learners’ engagement and meaning-making. Results: The findings revealed that visual semiotics serve as cognitive scaffolds, enhancing comprehension, reducing cognitive load, and supporting strategic learning. Emotional engagement was strengthened through the aesthetic, interactive, and meaningful design of visual materials, increasing motivation, confidence, and enjoyment. Behavioral engagement manifested in active participation, task completion, peer collaboration, and strategic attention to visual cues. Patterns of semiotic meaning-making emerged, showing that learners integrated visual, textual, and experiential information to construct understanding. Conclusions: Visual semiotics are integral to learner engagement in technology-mediated language education, functioning as active mediators of cognitive, emotional, and behavioral processes. Strategic integration of semiotic resources in instructional design, teacher training, and institutional management can enhance engagement, optimize learning outcomes, and support inclusive, multimodal digital learning environments. These findings highlight the need to reconceptualize engagement frameworks to account for multimodal semiotic affordances.